Deconstituting al-Qa'ida: CCO Theory and the Decline and Dissolution of Hidden Organizations. (November 2015) - Bean, Hamilton; Buikema, Ronald J.
This study reconceptualizes the decline and dissolution of hidden organizations using the four flows model of constitutive communication. Analyzing internal al-Qa'ida documents captured during the 2011 U.S. raid in Abbottabad, Pakistan, that killed Osama Bin Laden, this study explains how losses of control over the flows of membership negotiation, self-structuring, activity coordination, and institutional positioning have both reflected and reinforced al-Qa'ida's decline. Interventions inspired by a communicative constitution of organization (CCO) perspective are proposed as a way to accelerate al-Qa'ida's dissolution. The implications of the four flows model for both counterterrorism strategy and theorizing hidden organizations are discussed.